Poor glycemic control and associated factors among Type 2 Diabetes Mellitus patients at a Tertiary Health Care facility - Kumari, Rashmi; Singh, Neetu; Karoli, Ritu; Kandpal, Sunil Dutt; Singh, Shikhar; Ansari, Arshi; Singh, Chhaya; Usmani, Sarah; Singh, Kunver Abhimanyu (Indian Journal of Community Health, 2025)
Background: Poor glycemic control in type 2 diabetes mellitus (T2DM) patients is a major concern, as it can lead to serious complications. Understanding the factors contributing to poor glycemic control is essential for developing interventions to improve diabetes management and patient outcomes. Aim and Objective: This study aims to identify the factors associated with poor glycemic control among T2DM patients attending a tertiary health care facility. Setting and Design: A cross-sectional study was conducted in the Medicine Outpatient Department (OPD) of a tertiary care hospital. The study included 179 T2DM patients, selected using systematic random sampling. Material & Methods : Data were collected on socio-demographic characteristics, dietary habits, physical activity, medication adherence, and clinical parameters, including HbA1c levels. The study evaluated how these factors influenced glycemic control among the participants. Result: Factors such as lower educational attainment, non-vegetarian diet, high fasting and postprandial blood sugar levels, and elevated BMI were associated with poor glycemic control. Multivariate analysis revealed that a non-vegetarian diet (aOR: 2.35), random blood sugar >140 mg/dl (aOR: 3.91), postprandial blood sugar >140 mg/dl (aOR: 5.13), and education up to junior school level (aOR: 7.04) were independently linked to poor glycemic control. Conclusion: Addressing these factors through targeted interventions, such as educational programs and dietary adjustments, is essential for improving glycemic control and overall patient outcomes.